Recovery of platinum, palladium and gold from a pregnant cyanide heap leach solution, with the use of ion exchange resins - Schoeman, Ebon (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.